Agricultura Con Valor Agregado: ¿Es Lo Correcto Para Mí? - Edward A. Evans (EDIS)
FE-689, a 4-page article by Edward Evans, is the Spanish language version of "FE638/FE638: Value Added Agriculture: Is It Right for Me?" It explores the concept of value-added agricultural businesses and provides a set of preliminary questions which may help agricultural producers decide whether a particular value-added business is suitable for them. Includes references. Published by the UF Department of Food and Resource Economics, May 2007.